Pengaruh Keberadaan Alfamart dan Indomaret terhadap Eksistensi Warung Kecil di Kota Palopo - Dila Fadilla; Altri Wahida; Hapid Hapid (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The types of minimarkets Alfamart and Indomaret are retail businesses with a franchise concept that are currently experiencing rapid growth in Indonesia. The spread of minimarkets has entered residential areas. In this regard, this study aims to analyze the effect of the existence of Alfamart and Indomart on the existence of small stalls in the city of Palopo. The type of this research is field research with qualitative methods. The data collection techniques used are interviews, observation. Further analysis the data used is inductive. Based on the analysis of the data it is concluded that the existence of Alfamart and Indomaret in the city of Palopo has an impact on the income of the small shop in the city of Palopo. This causes unfair competition and even causes losses for small shop. Keywords: existence; Alfamart; Indomart; Small Stall